Impact of recent climate change and weather variability on the viability of UK viticulture – combining weather and climate records with producers' perspectives. (31st March 2016) - Nesbitt, A.; Kemp, B.; Steele, C.; Lovett, A.; Dorling, S.
Abstract: Background and Aims: From 2004 to 2013, the vineyard area in the United Kingdom (UK) increased 148%. Observed climate change and underlying weather variability were assessed for their influence on the development and viability of UK viticulture. Methods and Results: The perspectives of grapegrowers in the UK on climate change and weather variability were complemented by a quantitative analysis of climate and weather data (1954– 2013) for the main UK viticultural regions. The variability of growing season average temperature (GST) was calculated and also mapped using a modelling approach. Since 1993, GST has consistently been above the 13°C cool climate viticulture threshold. Alone, GST does not reliably assure yield predictability but does correlate more closely following the recent increasing UK focus on sparkling wine cultivars. June precipitation demonstrates the strongest relationship with yield. Conclusions: Increasing GST superficially suggests enhanced UK cool climate viticultural opportunities, but critically masks the additional impact of shorter term temperature and precipitation events and a high degree of inter‐ annual variability that continues to threaten productivity. A recent change in dominant UK vine cultivars appears to have increased viticultural sensitivity to inter‐ annual weather variability. Significance of the Study: This first quantitative and qualitative analysis of climate vulnerability in UK viticulture identifies threats and opportunities and helps steer studies of the impact of future climate change.